Simulating long-term occupational exposure to decabrominated diphenyl ether using C57BL/6 mice: Biodistribution and pathology. (June 2015) - Feng, Yan; Hu, Qingliang; Meng, Ge; Wu, Xiaomeng; Zeng, Weihong; Zhang, Xing; Yu, Yingxin; Wang, Yan
Graphical abstract: Highlights: A 2-year BDE-209-exposed mouse model was set up to simulate occupational exposure. BDE-209 preferentially accumulated in the ovary and uterus, liver and lung. Obvious pathological changes were observed in some organs of the exposed mice. No neoplastic lesions were observed in the exposed mice. Abstract: Decabrominated biphenyl ether (BDE-209) is a fully brominated diphenyl ether compound used widely as an additive brominated flame retardant in a variety of consumer products. In recent years, BDE-209 has been reported to be abundant and persistent in the environment, and comparatively high burdens have been found in occupational environmental compartments and exposed individuals. In the present study, an animal model for simulating long-term occupational exposure to BDE-209 was set up. Female C57BL/6 mice ( n = 10) were intragastrically administered BDE-209 at a dose of 800 mg kg −1 bw at 2-d intervals for 2 years with an internal blood level of approximately 200 ng mL −1, which was comparable to the high level of BDE-209 detected in the occupational population, and the biodistribution and biological effects were evaluated systematically. The results showed that large amounts of the chemical accumulated in most tissues, and the preferential organs were the ovary and uterus, liver and lung. Decreased survival was observed in the exposed mice. The subsequent pathological analysis revealed hepatomegaly in the exposed mice, accompanied by obvious histopathological changes in the liver, lung, brain, spleen, kidney and ovary. No neoplastic lesions were observed in this lifetime exposure study. Although the number of experimental mice was limited, our observations offer a comprehensive understanding of the chronic toxicology of BDE-209 after continuous high-dose exposure.